(untitled) (Journal of Asian Development Studies, 2018)
The main objective of this research is to check the impact of efficiency of families of working women and non-working women. For this purpose, 30 families were selected through simple random sampling and an interview schedule was used to collect the data. The results showed that there is a positive relationship between the efficiency of families and the batter compatibility of working women due to support and care of their families towards them. It can be concluded concern of family members to improve the mental satisfaction of women, whether working or non-working.